Efforts To Improve Football Shooting Skills With The Teams Games Tournament (TGT) Method For Grade X-2 Students of SMA Negeri 2 Bojonegoro - Afifatul, Mochammad Khoirul; Ramadhan, Nurman; Priadana, Benny Widya (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The difficulty faced in this study was that grade X-2 students at SMA Negeri 2 Bojonegoro were not good at shooting a ball. The purpose of this study was to see if the Teams Games Tournament (TGT) technique helped grade X -2 students of SMA Negeri 2 Bojonegoro improve their shooting skills while playing football. Classroom Action (PTK) is the research technique used here. A total of 36 students were included in this study, all in grades X-2. Information is gathered through the use of football shooting tests and visual recordings. The results of this study show that using Teams Games Tournament (TGT) to practice football shooting skills is effective. Cycle I had a 41.67 percent completion rate for football shooting skills; cycle II saw that figure rise to 86.11 percent.  Students of grades X and 2 of SMA Negeri 2 Bojonegoro experienced significant growth in shooting skills after participating in the Teams Games Tournament (TGT). The study's anticipated recommendation is to use the Teams Games Tournament (TGT) approach to improve goalscoring prowess in football matches.